1985
DOI: 10.1083/jcb.101.3.1086
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan synthesis is depressed during mitosis and elevated during early G1.

Abstract: [35S]Sulfate incorporation was measured in populations of Chinese hamster ovary cells enriched for mitotics, early G1 cells, and interphase monolayers or suspensions. Incorporation was determined by biochemical analysis of extracts and quantitative autoradiography of thick sections. 90% of [35S]sulfate was incorporated into glycosaminoglycan (GAG). Incorporation was depressed fourfold in mitotics and stimulated by from two-to three-fold in early G1 cells relative to mixed interphase cells. GAG synthesis was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 44 publications
(30 reference statements)
3
9
0
Order By: Relevance
“…Just 1 h after nocodazole removal the cells recovered their full GAG synthesizing capacity. At this stage, when most cells were entering early G 1 , we saw an overshoot of GAGs synthesis very similar to the one reported in the autoradiographic study of Preston et al (55).…”
Section: In Vitro Synthesis Of Gags By Rat Liver Golgi-incubation Of supporting
confidence: 73%
“…Just 1 h after nocodazole removal the cells recovered their full GAG synthesizing capacity. At this stage, when most cells were entering early G 1 , we saw an overshoot of GAGs synthesis very similar to the one reported in the autoradiographic study of Preston et al (55).…”
Section: In Vitro Synthesis Of Gags By Rat Liver Golgi-incubation Of supporting
confidence: 73%
“…previously reported (Preston et al, 1985); thus, the 3% contamination with interphase cells could give rise to secretion of no more than 9-120/o of GAG chains synthesized. Because we observed secretion of more than 85%/o, we conclude that the majority of GAG chains secreted is from the mitotic pool.…”
Section: Resultsmentioning
confidence: 96%
“…However, unlike interphase cells, in mitotic cells the elevation of [Ca2"], is not sustained and "5Ca2" influx is not stim-Introduction A wide range of membrane properties is altered during mitosis. This includes endocytosis (Berlin et aL, 1978), exocytosis (Hesketh et al, 1984), receptor recycling (Sager et al, 1984;Warren et al, 1985), glycosaminoglycan secretion (Preston et al, 1985), glycoprotein processing (Warren et al, 1983), and, we have shown recently, membrane signal transduction (Volpi and Berlin, 1988). In interphase HeLa cells, activation of the histamine Hi receptor leads to an elevation of intracellular free calcium ([Ca2+]D).…”
mentioning
confidence: 99%